Diagnostico hidráulico operativo de la planta de tratamiento de agua potable de municipio de Santuario Risaralda (2020)
The following work consists of diagnosing the drinking water plant of the municipality of Santuario (Colombia), an inspection of the current treatment system was carried out in order to detect possible shortcomings in the system; The basis of this project is aimed at gathering information through research carried out in this document, technical visits, documentation provided by the sanctuary E.S.P, hydraulic checks of existing infrastructure based on RAS 2000 resolution 0330 of 2017; The operation, quality of the water and the operation of the PTAP are diagnosed, based on resolution 2115 of 2007 current regulations that stipulate the parameters that affect the quality of the good object of the public service and the final disposal; Another procedure is to audit the administrative and technical operation processes carried out at the water treatment plant. The conclusions and recommendations of this type of research are summarized in the following paragraphs. Conclusions, the drinking water treatment plant complies with the parameters established by law and operates in accordance with the decrees that govern this type of public service companies, their collection, operation and administration permits are the order of the day. It was evident that the operators of the treatment plant had adequate adaptations to carry out work that was adequate to the requirements of the law. The served water is suitable for human consumption according to the rules and decrees that govern it. The chemical characteristics and microbiologies that may be a risk to human health, may require and its function of treatment and disinfection is optimal. Recommendations Analysis of their mixing processes and application of Cal type coagulant, since the mixers and dispensers are out of service and operators must do it manually. Analyze the physical configuration of the Alabama flocculator as it behaves like a cox flocculator. The water that comes from the source is a water with good chemical, physical and microbiological characteristics according to resolution 2115 of 2007 the regulatory quality, characteristics, basic instruments and frequencies of the control and surveillance system for the quality of water for human consumption and decree 1575 of 2007, which establishes the system for the protection and quality control of water for human consumption.